The 17-Gene Ethanolamine (eut) Operon of Salmonella typhimurium Encodes Five Homologues of Carboxysome Shell Proteins - Kofoid, Eric (American Society for Microbiology, 1999)
The eut operon of Salmonella typhimurium encodes proteins involved in the cobalamin-dependent degradation of ethanolamine. Previous genetic analysis revealed six eut genes that are needed for aerobic use of ethanolamine; one (eutR), encodes a positive regulator which mediates induction of the operon by vitamin B(12) plus ethanolamine. The DNA sequence of the eut operon included 17 genes, suggesting a more complex pathway than that revealed genetically. We have correlated an open reading frame in the sequence with each of the previously identified genes. Nonpolar insertion and deletion mutations made with the Tn10-derived transposable element T-POP showed that at least 10 of the 11 previously undetected eut genes have no Eut phenotype under the conditions tested. Of the dispensable eut genes, five encode apparent homologues of proteins that serve (in other organisms) as shell proteins of the carboxysome. This bacterial organelle, found in photosynthetic and sulfur-oxidizing bacteria, may contribute to CO(2) fixation by concentrating CO(2) and excluding oxygen. The presence of these homologues in the eut operon of Salmonella suggests that CO(2) fixation may be a feature of ethanolamine catabolism in Salmonella.